2018
DOI: 10.1071/cp18143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two groups of quinoa (Chenopodium quinoa Willd.) accessions with different seed colours for adaptation to the Mediterranean environment

Abstract: Agronomic and seed-quality traits in 17 quinoa (Chenopodium quinoa Willd.) accessions grouped according to seed colour (i.e. ochre and yellow) were investigated and compared with the white commercial cultivar Regalona-Baer. These accessions were previously selected from a range of accessions of diverse origin and seed colour for their potential value in a breeding program for cultivars adapted to the southern Italian environment. Field trials were conducted over 2 years in Foggia, southern Italy. The aim was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
16
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 45 publications
10
16
4
1
Order By: Relevance
“…Finally, the emerging findings support the sustainable management of quinoa in other regions with similar agroclimatic conditions, e.g. Mediterranean region, where quinoa is on a rapid expansion (Pulvento et al, 2010;De Santis et al, 2016;De Santis et al, 2018;Alvar-Beltrán et al, 2020).…”
Section: Accepted Papersupporting
confidence: 58%
“…Finally, the emerging findings support the sustainable management of quinoa in other regions with similar agroclimatic conditions, e.g. Mediterranean region, where quinoa is on a rapid expansion (Pulvento et al, 2010;De Santis et al, 2016;De Santis et al, 2018;Alvar-Beltrán et al, 2020).…”
Section: Accepted Papersupporting
confidence: 58%
“…Nitrogen fertilizer application rate strongly affected wheat crop growth, as also reported by De Santis et al. (2018). Annual application of different N fertilizer application rates over 17 yr significantly influenced wheat dry matter at different stages of development and leaf chlorophyll content and LAI at anthesis of wheat in 2018 and 2019 (Figure 2).…”
Section: Resultssupporting
confidence: 76%
“…However, other germplasm evaluation studies have also shown segregation in color and in other qualitative characteristics in quinoa (Del Castillo and Winkel, 2014;Alanoca and Machaca, 2017;Afiah et al, 2018;Al-Naggar et al, 2018;Morillo et al, 2020). The color characteristic in different plant structures was variable, and this variation is subject to the phonological stage of the crop, as reported in other studies (Noulas et al, 2017;De Santis et al, 2018). In the evaluation of the quantitative characteristics of the Piartal quinoa material in the five populations, according to the cv, the more variable characteristics were AHS (14.62-112.9%, P3, P2, respectively), DHS (23.53 -110.4% for P1 and P3, respectively), DP (33.52%, P2), LP (24.25% -31.23%, P4 and P2, respectively), DHI (28.27%, P4), AHI (26.62%, P5), LHI (22.54%, P1) and AP (22.26%, P1) ( Table 3).…”
Section: Resultssupporting
confidence: 69%